A Comparison of the Effectiveness of Short-Term Psychodynamic Psychotherapy and Cognitive-Behavioral Therapy on Health Anxiety and Differentiation of Self in Patients with Coronary Artery Disease in Hamadan City - Ebrahimkhani, Mehdi; Rezaei Jamolouei, Hasan; Ariapooran, Saeed; Yaghoobi , Abolghasem (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to compare the effectiveness of short-term psychodynamic psychotherapy and cognitive-behavioral therapy in reducing health anxiety and improving self-differentiation in patients with coronary artery disease in Hamadan. Methods and Materials: A semi-experimental research design with a pretest-posttest format and control group was used. The statistical population included all coronary artery disease patients aged 35 to 55 referred to Farshchian Hospital in 2024. Forty-five eligible participants were selected through convenience sampling and randomly assigned to two intervention groups (short-term psychodynamic psychotherapy and cognitive-behavioral therapy) and one control group (n = 15 per group). Both interventions were delivered in group format over 12 sessions within 90 days. Data were collected using the Health Anxiety Inventory (Salkovskis et al., 2002) and the Differentiation of Self Inventory (Skowron & Friedlander, 1998). Data analysis was conducted using univariate ANCOVA and Bonferroni post hoc tests in SPSS version 25, with assumptions confirmed prior to analysis. Findings: ANCOVA results showed that both psychotherapeutic interventions significantly reduced health anxiety compared to the control group (p < 0.05), with no significant difference between the two treatment groups. For self-differentiation, significant differences were found among all three groups, with the psychodynamic group showing significantly higher gains than both the cognitive-behavioral and control groups (p < 0.001). Similar patterns were observed across subscales, including emotional reactivity, I-position, emotional cutoff, and fusion with others, where the psychodynamic approach demonstrated greater effect sizes. Conclusion: Both short-term psychodynamic psychotherapy and cognitive-behavioral therapy are effective in reducing health anxiety in cardiac patients; however, the psychodynamic approach appears superior in enhancing deeper psychological constructs such as self-differentiation. These findings highlight the importance of addressing both symptom reduction and personality development in psychosomatic treatment planning.